Productivity of indigenous pigs in communal production systems of Sekhukhune District in Limpopo Province - Soana, Legoai Winter (My University, 2013)
A study was conducted to determine environmental and socio-economic factors affecting pig productivity in communal areas. A questionnaire was administered to collect data on production environment and socio-economic variables underlying productivity in Sekhukhune District. Production environment included explanatory sex of the piglet, season of birth, feed type, housing type, municipality, herd size, health management and disease prevalence, while socio-economic variables included household size and gender of head of household, age, level of education and employment status. A total of 112 farmers were interviewed from 25 villages. Data on productivity were collected using production record sheets. Performance parameters in the production sheets included litter size, litter weight, individual birth weight, live weight and mortality. Monitoring was done from birth date to subsequent farrowing date at the farmers’ backyard. One farrowing sow per producer was used and a total of 605 piglets were monitored in the municipalities. A total of 1468 indigenous pigs were kept for breeding with 104 castrated males occupying less space in the production system within the district. Feeding was characterized by kitchen wastes or garbage at total of 78 farmers, 22 feeding garbage and grains, and only 12 farmers feeding concentrate. There was measles prevalence in the production system with a total of 41 farmers treating the suspected pigs; the larger number (71) however, did not treat pigs. Health did not affect (P>0.05) litter size and birth weight. Birth weight was affected (P>0.05) by disease prevalence, herd size, household head sex, age and education, and family size. Mean litter size was 4.38 piglets at birth, mean litter weights of 5.78 kg, mean birth weight of 1.32, and mean mortality at 2.31 piglets. Season, feed, municipality, diseases, herd size, the age, education and employment of household head affected pre-weaning mortality (P<0.05). v There is statistical evidence (P<0.05) that there were associations between litter size, litter weight, birth weight and mortality and the feed, municipality, diseases, herd size, the age, education and employment of household head respectively. There were deficiencies in the entire production system with regards to pig management practices, feeding practices, housing of pigs, breeding systems, herd composition and size and the general practices in the keeping of the pig herds by majority of pig producers. These deficiencies call for introduction of sound pig management plans in communal areas which should include keeping pigs indoor to account for the healthy herd, proper feeding and sound breeding plans.
Thesis (M.A. (Agricultural Management)) -- University of Limpopo, 2013
Keywords: Pigs; Breeding; Swine -- Breeding -- South Africa -- Limpopo; Swine -- Feeding and feeds